2022
DOI: 10.1002/cam4.5505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of preoperative neutrophil‐lymphocyte ratio and platelet‐lymphocyte ratio in the prognosis of resected early‐stage patients with non‐small cell lung cancer: A meta‐analysis

Abstract: Background Poor prognosis is linked to peripheral blood levels of preoperative platelet‐lymphocyte ratio (PLR) and neutrophil‐lymphocyte ratio (NLR) in many advanced cancers. Nevertheless, whether the correlation exists in resected early‐stage cases with non‐small cell lung cancer (NSCLC) stays controversial. Consequently, we performed a meta‐analysis to explore the preoperative NLR and PLR's prognostic significance in early‐stage patients with NSCLC undergoing curative surgery. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Improvements in the accuracy and prognostic value of liquid biopsy thanks to AI have been reported in other, nonthoracic malignancies, such as ovarian cancer 38 . Similar investigations are currently underway in lung cancer, analyzing biomarkers which can be drawn from peripheral blood samples to guide diagnosis and individualize treatment recommendations 39,40 …”
Section: Advancements In Screening and Diagnosismentioning
confidence: 88%
See 1 more Smart Citation
“…Improvements in the accuracy and prognostic value of liquid biopsy thanks to AI have been reported in other, nonthoracic malignancies, such as ovarian cancer 38 . Similar investigations are currently underway in lung cancer, analyzing biomarkers which can be drawn from peripheral blood samples to guide diagnosis and individualize treatment recommendations 39,40 …”
Section: Advancements In Screening and Diagnosismentioning
confidence: 88%
“…38 Similar investigations are currently underway in lung cancer, analyzing biomarkers which can be drawn from peripheral blood samples to guide diagnosis and individualize treatment recommendations. 39,40…”
Section: The Role Of Ai In Lung Cancer Diagnosismentioning
confidence: 99%
“…A recent meta-analysis that examined 21 studies has concluded that preoperative elevated NLR and PLR levels may act as prognostic markers in only early stage NSCLC patients that were operated while our study has the same conclusion in all stages. [28] Likewise another study that has investigated again only the operated NSCLC patients also concluded that both NLR and PLR are related to survival but PLR demonstrates a greater prognostic value than NLR. [29] An interesting study which investigated newly diagnosed stage IV NSCLC patients a relationship was found between depressive symptoms and NLR,PLR increase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, more CAR‐T studies have focused primarily on NSCLC 141,142 . The most common target antigens of NSCLC include human EGFRs, mesothelin, mucin 1, PD‐L1, 143 CEAs, 144 and HER2 145 . As a result, these antigens are potentially novel targets for NSCLC treatment 146,147 …”
Section: Development Trend Of Clinical Immunotherapy Based On Dcs And...mentioning
confidence: 99%